Unsettling Identity: Reading That Deadman Dance Novel by Kim Scott - Shofi Mahmudah Budi Utami (Journal of English Language Studies, 2021)
The reviving of the presence, existence, and eugenics of the Aborigines become pivotal issue to be brought up in the literature. Since the coming of the settlers, the Aborigines have seemed to experience shifting identity; living as a nominal population over the settlers; and later on becoming the ones who are attached with the ‘exotic’ due to their uniqueness and scarcity in number compared to the majority. This condition, from being the natives who own the land into those who become the ‘rare’ in their own land, provokes crucial issues related to the Aboriginal identity, which is challenging to be further discussed. Through That Deadman Dance, Scott tries to resurrect the Aborigine’s identity, especially Noongar, in the midst of disappearing Aboriginal communities. This article is aimed at revealing the identity of Noongar people by selecting and grouping the textual data in the novel which portray the Aborigines cultural experience and their indigenity. Later on, the data were investigated based on Muecke’s concept of connectedness to approach the problem. Accordingly, the narrative presented by Scott indicates that he has offered an alternative to view Aborigine’s identity which is potentially unsettling; thus, this finding seems to challenge the prescribed identity of Noongar corresponded by the major society.